Antimitogenic effects of HDL and APOE mediated by Cox-2–dependent IP activation - Kothapalli, Devashish (American Society for Clinical Investigation, 2004)
HDL and its associated apo, APOE, inhibit S-phase entry of murine aortic smooth muscle cells. We report here that the antimitogenic effect of APOE maps to the N-terminal receptor–binding domain, that APOE and its N-terminal domain inhibit activation of the cyclin A promoter, and that these effects involve both pocket protein–dependent and independent pathways. These antimitogenic effects closely resemble those seen in response to activation of the prostacyclin receptor IP. Indeed, we found that HDL and APOE suppress aortic smooth muscle cell cycle progression by stimulating Cox-2 expression, leading to prostacyclin synthesis and an IP-dependent inhibition of the cyclin A gene. Similar results were detected in human aortic smooth muscle cells and in vivo using mice overexpressing APOE. Our results identify the Cox-2 gene as a target of APOE signaling, link HDL and APOE to IP action, and describe a potential new basis for the cardioprotective effect of HDL and APOE.